Higher education and Silicon Valley : connected but conflicted - Scott, W. Richard; Kirst, Michael W. (Johns Hopkins University Press, 2017)
"Universities and colleges often operate between two worlds: higher education and economic systems. It is impossible to understand how current developments are affecting colleges without attending to the changes in both the higher education system and in the economic communities in which they exist. W. Richard Scott, Michael W. Kirst, and colleagues focus on the changing relations between colleges and companies in one vibrant economic region: the San Francisco Bay Area. Colleges and tech companies, they argue, have a common interest in knowledge generation and human capital, but they operate in social worlds that substantially differ, making them uneasy partners. Colleges are a part of a long tradition that stresses the importance of precedent, academic values, and liberal education. High-tech companies, by contrast, value innovation and know-how, and they operate under conditions that reward rapid response to changing opportunities. The economy is changing faster than the postsecondary education system."--The cover.